Penerapan Metode C4.5 dalam Prediksi Penjualan Tim Bev 1 pada PT. Surya Pangan Sejahtera Bekasi Jawa Barat - Ruliansyah, Muhammad Jauhar; Betty, Mesra (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
The C4.5 method is a machine learning algorithm used to create decision trees in data analysis. This research aims to apply the C4.5 Method in predicting the Bev Team 1 target sales at PT. Surya Pangan Sejahtera in Bekasi, West Java. This research utilizes historical sales data, internal and external factors that influence sales, as well as sales targets set by the company. The C4.5 method is used to produce a decision tree that can help in understanding the key factors that influence the sales of the Bev 1 team. The results of this research show that the C4.5 Method can be used to predict the sales of the Bev 1 team with fairly high accuracy. The decision tree generated by this algorithm helps identify the factors that most influence sales, such as sales location, season, promotions, and others. By understanding these factors, companies can take more effective action in achieving their sales targets. This research provides valuable insight for PT. Surya Pangan Sejahtera in managing the Bev 1 team and achieving their sales targets. The C4.5 method can be a useful tool in data analysis and future sales predictions, as well as helping companies to make better decisions in optimizing the performance of their Bev 1 teams.